PENGARUH UKURAN PERUSAHAAN, KINERJA KEUANGAN, FINANCIAL LEVERAGE DAN MANAJEMEN LABA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2016-2018 - Reynaldi Aziz; Noor Shodiq Askandar; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine the effect of Company Size, Financial Performance, Financial Leverage and Earnings Management on Disclosure of Corporate Social Responsibility in Manufacturing Companies Listed on the IDX 2016-2018. Based on the calculation data, it was found that 61 companies were selected as samples. The results of the analysis using multiple linear regression analysis show that Financial Performance and Financial Leverage have a significant effect on the disclosure of Corporate Social Responsibility simultaneously. Partially the test results show Company Size, Financial Performance, Financial Leverage has a significant effect on disclosure of Corporate Social Responsibility. The partial test results show that Earnings Management does not have a significant effect on disclosure of Corporate Social Responsibility.Keywords : Company Size, Financial Performance, Financial Leverage, Earnings Management, Corporate Social Responsibility.